2017
DOI: 10.4103/jcvjs.jcvjs_57_17
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prevertebral soft tissue swelling on dysphagia after anterior cervical discectomy and fusion using a rectangular titanium stand-alone cage

Abstract: Background:Postoperative oropharyngeal complications such as dysphagia after anterior cervical spine surgery are some of the least discussed surgery-related complications. The purpose of this retrospective study is to investigate the incidence and possible risk factors for 30-day postoperative dysphagia after anterior cervical discectomy and fusion (ACDF).Materials and Methods:This study included 152 consecutive patients who underwent 1- or 2-level ACDF using a rectangular titanium stand-alone cage in our inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Cervical tissues are dissected and drawn during anterior cervical fixation, which may cause local hyperemia or edema of tissues that manifests as PVST swelling in lateral radiographs. Postoperative PVST swelling may further compress the anterior pharynx, esophagus, or trachea, resulting in complications including dysphagia and respiratory tract obstruction (18)(19)(20)(21)(22)(23)(24)(25). PVST swelling peaks at about day 3 after the operation and gradually alleviates as time went on.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical tissues are dissected and drawn during anterior cervical fixation, which may cause local hyperemia or edema of tissues that manifests as PVST swelling in lateral radiographs. Postoperative PVST swelling may further compress the anterior pharynx, esophagus, or trachea, resulting in complications including dysphagia and respiratory tract obstruction (18)(19)(20)(21)(22)(23)(24)(25). PVST swelling peaks at about day 3 after the operation and gradually alleviates as time went on.…”
Section: Resultsmentioning
confidence: 99%
“…[4] Yamagata et al found that patients with C3 prevertebral soft tissue swollen at 2 or 3 days after surgery were 8.7 times more likely to have postoperative dysphagia. [18] Patients with C4 prevertebral soft tissue swelling at 2 or 3 days after surgery were 4.7 times more likely to have postoperative dysphagia. Yagi et al found that prevertebral soft tissue edema was related to severe dysphagia and odynophagia after anterior cervical discectomy and fusion.…”
Section: Discussionmentioning
confidence: 99%
“…The present study determined that postoperative changes in radiographic swelling and air indices are not different following ACDF with or without anterior plating. Prevertebral soft tissue swelling (PSTS) has been previously reported to correlate with dysphagia after ACDF [35,36]. As postoperative swallowing function was similar for Plate and Cage patients, it is intuitive that swelling and air indices would also be similar between cohorts.…”
Section: Discussionmentioning
confidence: 99%